Penggunaan Aerated Compost Tea Dari Bahan Kompos Seresah Untuk Nutrisi Dan Perlindungan Tanaman - Salman Farisi; Bambang Irawan; Suratman; Hendri Busman (AMMA : Jurnal Pengabdian Masyarakat, 2024)
One product of composting technology that also growing rapidly is the manufacture of compost tea (CT). CT is an oxygenated compost water extract obtained through aeration in the liquid phase. The process of making CT with this method is called Aerated Compost Tea (ACT). ACT is a compost water extract containing dissolved nutrients and growth hormones. In addition to functioning as a source of nutrients, ACT can also improve the soil ecosystem for the growth of decomposing microbes that can support soil fertility, improve soil physical and biological properties, improve microbial activity, and can also increase plant resistance to pathogens. ACT provides dissolved nutrients that are more quickly absorbed by plants and at the same time provides biopesticides to prevent or inhibit infection by pathogens that cause plant diseases. This Community Service activity is the development of science and technology from the results of research that has been carried out. The results of Community Service show quite good results, namely there is an increase of about 33.35% from the initial understanding. This is quite interesting because the initial understanding of ACT was low, at level of 60.54. The explanation given by the Community Service team, able to be understood by the target audience well so that their understanding increased to 78.02.